AB0550 PHENOTYPE OF BIOPSY-PROVEN PATIENTS WITH PRIMARY SJÖGREN SYNDROME LACKING RO AUTOANTIBODIES: HIGH FREQUENCY OF DRYNESS SYMPTOMS WITH LOW SYSTEMIC ACTIVITY (BIG DATA SJÖGREN PROJECT). (June 2019) - Retamozo, Soledad; Acar-Denizli, Nihan; Ng, Wan Fai; Horváth, Ildiko Fanny; Rasmussen, Astrid; Seror, Raphaèle; Xiaomei, LI; Baldini, Chiara; Gottenberg, Jacques-Eric; Sandhya, Pulukool; Quartuccio, Luca; Priori, Roberta; et al.
Abstract : Objectives: To analyze the clinical phenotype of primary Sjögren syndrome (SjS) with focal lymphocytic sialadenitis (FLS) without Ro autoantibodies (FLS+/Ro-). Methods: The International Big Data Sjögren Project was designed in 2014 to take a "high-definition" picture of the primary SjS at diagnosis (2002 criteria) by merging international databases. 2716 FLS+/Ro- patients were compared with 8315 Ro+ patients Results: FLS+/Ro- patients were predominantly White (82% vs 77%), had a higher frequency of oral (97% vs 92%) and ocular (95% vs 91%) dryness, a lower frequency of ANA (60% vs 87%), hypocomplementemia (13% vs 23%), rheumatoid factor (26% vs 56%), cryoglobulins (5% vs 9%), a lower mean ESSDAI score (4.6 vs 6.6), and a lower systemic activity in the constitutional, lymphadenopatic, glandular, cutaneous, renal, hematological and biological domains (p<0.001 for all comparisons). Abnormal salivary flows and ANA remained significant independent variables after adjustment by age and gender. Conclusion: Biopsy-proven primary SjS with negative anti-Ro antibodies is characterized by high frequency of sicca symptoms, mild immunological profile and low systemic activity. Disclosure of Interests: Soledad Retamozo: None declared, Nihan Acar-Denizli: None declared, Wan Fai Ng: None declared, Ildiko Fanny Horváth: None declared, Astrid Rasmussen: None declared, Raphaèle Seror Grant/research support from: Pfizer, Consultant for: Bristol-Myers Squibb, Pfizer, Amgen, Eli Lilly, Roche, Celgene, GlaxoSmithKline, MedImmune, Xiaomei Li: None declared, Chiara Baldini: None declared, Jacques-Eric Gottenberg Grant/research support from: Bristol-Myers Squibb, Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Lilly, Pfizer, Sanofi-Genzyme, UCB Pharma, Consultant for: Bristol-Myers Squibb, Eli Lilly, UCB, Sanofi-Genzyme, Pfizer, Pulukool Sandhya: None declared, Luca Quartuccio: None declared, Roberta Priori: None declared, Gabriela Hernandez-Molina: None declared, Berkan Armagan: None declared, Aike A. Kruize: None declared, Seung-Ki Kwok: None declared, Marika Kvarnstrom: None declared, Sonja Praprotnik: None declared, Damien Sene: None declared, Roberto Gerli: None declared, Roser Solans-Laqué: None declared, Maureen Rischmueller Consultant for: Abbvie, Bristol-Meyer-Squibb, Celgene, Glaxo Smith Kline, Hospira, Janssen Cilag, MSD, Novartis, Pfizer, Roche, Sanofi, UCB, Thomas Mandl: None declared, Yasunori Suzuki: None declared, David Isenberg: None declared, Valeria Valim: None declared, Agata Sebastian: None declared, Gunnel Nordmark: None declared, Hendrika Bootsma: None declared, Hideki Nakamura: None declared, Roberto Giacomelli Grant/research support from: Pfizer, Actelion, Speakers bureau: Actelion, Bristol-Myers Squibb, Merck Sharp & Dohme, Abbvie, Pfizer, Sobi, Roche, Valerie Devauchelle-Pensec Grant/research support from: Roche-Chugai, Speakers bureau: MSD, BMS, UCB, Roche, Benedikt Hofauer Consultant for: Consultant for Galvani Bioelectronics for the area of sleep disorders., Michele Bombardieri Grant/research support from: Celgene, Consultant for: Medimmune, Virginia Fernandes Moça Trevisani: None declared, Daniel Hammenfors: None declared, Sandra Pasoto: None declared, Tamer A Gheita: None declared, Fabiola Atzeni: None declared, Jacques Morel: None declared, Cristina Vollenveider: None declared, Sandra Consani-Fernández: None declared, Xavier Mariette Consultant for: Honorarium from Bristol-Myers Squibb, GlaxoSmithKline, Gilead, Janssen, Pfizer, UCB, Manuel Ramos-Casals: None declared, Pilar Brito-Zerón: None declared